Effectiveness of Teaching Methodologies in Undergraduate Commerce Colleges: Thematic Review of Literature - Philip, Mohan P.; K., Ramya (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2018)
As a branch of education, Commerce is a subject that imparts Knowledge and experience of business world at large in all its manifestations. Commerce education at the university level in India made its beginning in 1913 when Sydenham college of Commerce and Economics was established by the Government in Mumbai. Thereafter, a large number of prestigious business houses used to absorb commerce degree from other reputed colleges of commerce in Mumbai. The increase demand for commerce education has been due to Rapid industrialization, Expansion of Banking and Insurance Industries, Introduction of various regulations in commercial activities, taxation laws, etc., Commerce teaching is a professional service which affects the revenue stream but also the reputation of the institution leading to satisfaction of students who is one of the most important stakeholder. A good commerce teacher should not only teach but also help students to analyse and find out the problems felt by students in their learning. To keep the teaching effective, commerce teachers need to use few innovative and effective methodologies in their teaching. Teachers are facilitators for the commerce students. To facilitate they should share the practical and theoretical knowledge, what they acquired during their education and experiences. This paper addresses the different teaching methodologies and its effectiveness in teaching commerce subjects.